PENERAPAN MODEL PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 002 BANTAYAN KECAMATAN BATU HAMPAR - Sari Mala Dewi; Zetra Hainul Putra; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research was aimed to increase learning process and students’ acheivement of social lesson in V grade year of 2015/2016. The subject of this research is students grade V of SDN 002 Bantayan which is total of 34 students, consisted of 14 boys and 20 girls. This was a classroom action research which has two cycles which was conducted on March 26th to April 9th, 2015. The data shown either learning process or students’ acheivement increased. This was found from students’ and teacher’s scores in learning process. First cycle at the first meeting teacher’s activity was 58,3% categorized as enough and increased 8,3% at the second meeting as 62,5% categorized as good. Meanwhile at the second cycle at the first meeting the percentage of teacher’s activity increseased as 79,1% categorized as good and in the second meeting it increased as 16,6 % so the percentage became 95,8% categorized as very good. While student’s activities in learning process also increased. At the first cycle in the first meeting, the percentage of students’ activities was 54,1% categorized as enough and the second meeting it increased as 12,5% so became 66,6% categorized as good. At the second cycle in the first meeting it increased to 75% categorized as good. At the second meeting the percentage of students’ activities increased as 20,8% became 95,8% categorized as very good. How ever, students’ achievement also increased. The basic score incresead 17,22% to the score of examination in first cycle. Clasical completeness was 85,29% with average score 74,12. The average score also increased from the basic score to the score of examination in the second cycle about 22,33% with 32 students passed the test. Clasical completeness was 94,12% with the average score 77,35. Bassed on this data, it can be concluded that the implementation of cooperative learning models can increase social science learning result of grade V SDN 002 Bantayan.Keywords: Cooperative Learning Model, Social Science Learning Result